The Use of Emoji Across Age Groups: Insights from the Exchanges of Music Fandom in Twitter/X Discourse - Palacios Martínez, Ignacio Miguel; Núñez Pertejo, Paloma (Complutense Journal of English Studies, 2025)
Emoji have recently gained in popularity in digital communication. However, while age has been considered in emoji studies, mainly in relation to frequency and preference, its role in shaping emoji meaning, its connection with the topic in question, position and pragmatic value within Twitter/X discourse remains underexamined. This study addresses the gap by considering how different age groups use emoji in the Twitter/X discourse context of music fandom. Two samples of data are analysed: one consisting of posts from the accounts of three British rappers in their mid-twenties, and the other comprising tweets from three well-known London singers born in the 1950s and 1960s. Findings suggest that age, which has consistently been found to play a significant role in offline communication, also influences the use of emoji in Twitter/X. Indeed, very notable differences here were observed between the two groups. The categories of ‘Hearts’, ‘Music & Films’ and ‘Celebrations’ occur more frequently among the mature adults of the sample, whereas those of ‘Fire’ and ‘Hands & Fingers’ are more commonly used by the younger adults. Additionally, the former group seems to favour ‘standalone’ emoji as responses to previous messages. Pragmatically, subjective functions are more prominent among the participating mature adults, whereas intersubjective functions are more frequent with the younger users.